Non-invasive prenatal screening using cell-free fetal DNA : how good a screening assay is this ? - Tan, Christina En Hui (2016)
Prenatal diagnosis provides expectant mothers with important information which may affect subsequent pregnancy management. Karyotyping and fluorescence in situ hybridisation (FISH) following chorionic villus sampling (CVS) or amniocentesis are the gold standards in detecting genetic abnormalities. However, these procedures are invasive with up to 1% increased miscarriage risk. Recently, the non-invasive prenatal screening (NIPS) using cell-free fetal DNA (cffDNA) assay has been proposed as a new screening tool. It has higher accuracy levels than current first-line screening and obviates invasive techniques. Hence, this study aims to compare the performance of this new assay with invasive diagnostic tests. A retrospective analysis was performed on 299 NIPS using cffDNA cases from September 2013 to July 2016. If a follow-up invasive procedure was performed, the karyotyping and/or FISH result was obtained. Of the 17 patients who opted for an invasive procedure, 10 were true positives, 3 true negatives, and 4 false positives. 2 patients cancelled the assay due to repeated assay failure and false negatives cannot be ruled out as informative birth outcomes were not available for correlation. The results show that the NIPS using cffDNA assay remains a screen and confirmatory invasive diagnostic testing is still required for high risk NIPS results.